Interreligious Dialogue For Conflict Prevention - Zarkasi, Ahmad; Ruslan, Idrus; Syafril, Syafrimen; Agustam, Agustam; Ramli, Azhar Jaafar (KALAM, 2023)
Interreligious dialogue possesses external and internal critical functions. Such dialogue promotes a new resolution for a sustainable community as stable and dynamic interreligious understanding and its application are gained among the plural society. The objective of the study is to reveal whether the interreligious dialogue is a potential in managing conflict prevention. The research uses multi case single-site exploratory case study. Primary data was collected through observation as well as snowballing technique and in-depth interview conducted to village leaders and religious leaders in Punduh Pidada, District of Pesawaran in which the community is religiously diversed. They come from various religions; Islam, Christian and Catholic. Meanwhile secondary data was obtained through document analysis of various religious books, holy books and any documents related to the study. Data was qualitatively analysed by using the NVIVO 10 software. Contributions: Indonesia is a country with the most diverse number of ethnicities, race, languages, cultures and religions in the world, that diversity is wealth and assets for a nation, but if not properly maintained it will cause conflicts in society. Three ways to resolve conflict issues as described in this study can be used as examples and references by the government in overcoming and dealing with conflicts among society in Indonesia, especially conflicts related to religious issues.